Upaya Pengurangan Dampak Lingkungan melalui Pemanfaatan Sampah Plastik menjadi Bantal dan Paving Block di Desa Pogalan - Muhammad Rauf Bowo Laksono; Naufal Bari Nugroho; Ibra Ismail Sani; Muhlis Firmansyah; Mohammad Shodiq Musarrof; Aisyah Lashinta Dewi; Zera Vivi Anjani; Salsabella Vanisa Putri; Nafisah Azhar Anindita; Laila Nurul Hidayati; Rahma Wulan Idayanti (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
The problem of plastic waste in Gandan Hamlet, Pogalan Village, is becoming an increasingly urgent environmental issue that requires sustainable management. Unmanaged waste can pollute the soil, air, and water, and threaten public health. In response to this situation, Tidar University Community Service (KKN) students implemented an innovative community-based waste management program. The main focus of this program is to utilize plastic waste into products with utility and sales value, namely plastic-filled pillows and Eco-Paving Blocks. This activity was carried out through a participatory approach by actively involving the community at every stage, from outreach and education to technical training on the collection, sorting, and processing of plastic waste. The education provided concerns the dangers of plastic waste to the environment and the importance of recycling as an alternative solution. Making pillows from plastic filling was chosen because the process is simple, inexpensive, and can be done by housewives. Meanwhile, Eco-Paving Blocks are the result of utilizing mixed plastic waste as an environmentally friendly and durable building material. This program has succeeded in reducing the volume of plastic waste in the surrounding environment, while raising public awareness of the importance of environmental conservation. Furthermore, this activity opens up new economic opportunities for the community by creating creative products from waste. Evaluation results show that the community-based waste management model is effective in fostering community independence in waste processing, creating a cleaner environment, and encouraging a culture of sustainable living at the village level. The success of this program is expected to serve as an example for replication in other areas with similar challenges. Continued support from the village government and cross-sector collaboration are key to this initiative's continued growth and long-term impact.